SPECT/CT imaging reveals CNS-wide modulation of glymphatic cerebrospinal fluid flow by systemic hypertonic saline - Tuomas O. Lilius; Marko Rosenholm; Laura Klinger; Kristian Nygaard Mortensen; Björn Sigurdsson; Frida Lind-Holm Mogensen; Natalie L. Hauglund; Malthe Skytte Nordentoft Nielsen; Tomi Rantamäki; Maiken Nedergaard (iScience, 2022)
Summary: Intrathecal administration enables central nervous system delivery of drugs that do not bypass the blood-brain barrier. Systemic administration of hypertonic saline (HTS) enhances delivery of intrathecal therapeutics into the neuropil, but its effect on solute clearance from the brain remains unknown. Here, we developed a dynamic in vivo single-photon emission computed tomography (SPECT)/computed tomography (CT) imaging platform to study the effects of HTS on whole-body distribution of the radiolabeled tracer 99mTc-diethylenetriaminepentaacetic acid (DTPA) administered through intracisternal, intrastriatal, or intravenous route in anesthetized rats. Co-administration of systemic HTS increased intracranial exposure to intracisternal 99mTc-DTPA by ∼80% during imaging. In contrast, HTS had minimal effects on brain clearance of intrastriatal 99mTc-DTPA. In sum, SPECT/CT imaging presents a valuable approach to study glymphatic drug delivery. Using this methodology, we show that systemic HTS increases intracranial availability of cerebrospinal fluid-administered tracer, but has marginal effects on brain clearance, thus substantiating a simple, yet effective strategy for enhancing intrathecal drug delivery to the brain.